Pangako Sa ‘Yo: Kompensasyon sa mga Biktima ng Batas Militar - Domingo, Rodrigo C.; Buenaventura-Mangahas, Fe; Melecio, Rita; Mendoza, Meynardo P.; Diciembre, Roberto; Gomez-Dumpit, Karen (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Proceedings of the second "Marcos Pa Rin!" forum.